2017
DOI: 10.30935/scimath/9511
|View full text |Cite
|
Sign up to set email alerts
|

Profiling teachers based on their professional attitudes towards teaching responsible research and innovation

Abstract: In order to facilitate policy-driven reforms in science education, it is important to understand how teaching innovations diffuse among teachers and how that adoption process can be catalysed. Little is known about the set of attitudes that makes teachers early or late adopters. In this study, the Concerns-Based Adoption Model (C-BAM) was employed as a framework for analysing teachers' interests, concerns, worries and enthusiasm. We argue that the questionnaire typically used with C-BAM suffers from a ceiling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The distinction between positive teachers (Profile 2 and 4) and critical teachers (Profile 1 and 3) corresponds with the education innovation literature (Kopcha et al, 2016;Scherer et al, 2020;Vocht & Laherto, 2021), and it could reflect more-general attitudes toward educational technologies (Garone et al, 2019;Jimoyiannis & Komis, 2007;MacIntyre et al, 2020). However, in this case, teachers' attitudes toward online education are likely to be coloured by their experience of the crisis, such as the involuntariness of the transition to online education (Anderson et al, 2006;Debuse et al, 2008;Garone et al, 2019) and the experienced level of stress (Akour et al, 2020;Hew et al, 2020;Hodges et al, 2020).…”
Section: Interpretation Of the Profilesmentioning
confidence: 68%
“…The distinction between positive teachers (Profile 2 and 4) and critical teachers (Profile 1 and 3) corresponds with the education innovation literature (Kopcha et al, 2016;Scherer et al, 2020;Vocht & Laherto, 2021), and it could reflect more-general attitudes toward educational technologies (Garone et al, 2019;Jimoyiannis & Komis, 2007;MacIntyre et al, 2020). However, in this case, teachers' attitudes toward online education are likely to be coloured by their experience of the crisis, such as the involuntariness of the transition to online education (Anderson et al, 2006;Debuse et al, 2008;Garone et al, 2019) and the experienced level of stress (Akour et al, 2020;Hew et al, 2020;Hodges et al, 2020).…”
Section: Interpretation Of the Profilesmentioning
confidence: 68%
“…14 Education innovation projects are driven by both top-down management decisions and bottom-up local initiatives. 15 However, studies have shown that many of these projects fail to generate comprehensive and sustainable innovation. 16 Lembani, et.al., caution against the unsupervised and ill-conceived use of education innovation projects for technological implementation, as it may lead to stagnation and false claims of innovation by organizations.…”
Section: Literature Review Digital Technology In South African Schoolsmentioning
confidence: 99%
“…Most teachers' professional development programmes and courses aim at diffusing educational innovations, and research-based development of such programmes has typically addressed teachers' beliefs, attitudes and concerns facilitating or hindering that diffusion [11][12][13]. Although these studies tend to focus on teachers' adoption of a reform/innovation, several studies on teachers' professional development have acknowledged teachers' role, not only in putting an innovation into operation but also changing and refocusing it [12,14]. However, these studies still frame the role of the teacher as a sort of "fidelity" [9] to a reform imported from elsewhere.…”
Section: Introductionmentioning
confidence: 99%